43.6k views
3 votes
1. (4.8x + 15.5) + (2.1x - 12.2)

2. (7x + 8) - (3x + 12)

3. (0.5x + 0.74) + (0.5x - .25)

2 Answers

5 votes
1. (4.8x + 15.5) + (2.1x - 12.2) = 4.8x + 15.5 + 2.1x - 12.2 = 6.9x + 3.3
2.
(7x + 8) - (3x + 12) = 7x + 8 - 3x - 12 = 4x - 4
3.
(0.5x + 0.74) + (0.5x - 0.25) = 0.5x + 0.74 + 0.5x - 0.25 = x + 0.49
User Bakavic
by
5.7k points
4 votes
Hey there :)

In all these questions, we should combine the like terms to simplify

1) (4.8x + 15.5) + (2.1x - 12.2)
4.8x + 2.1x + 15.5 - 12.2

6.9x + 3.3

2) (7x + 8) - (3x + 12)
7x - 3x + 8 - 12

4x - 4

3) (0.5x + 0.74) + (0.5x - 0.25)
0.5x + 0.5x +0.74 - 0.25

x + 0.49
User Jaymee
by
6.5k points